Bottlenecks and opportunities in immunotherapy for glioma: a narrative review. Issue 4 (31st December 2022) - Shi, Ying; Wu, Mengwan; Liu, Yuyang; Chen, Ling; Bian, Xiuwu; Xu, Chuan
Abstract : Glioma is the most aggressive brain tumor having invasive ability and a highly heterogeneous phenotype. Many patients with glioma respond poorly to traditional surgery or temozolomide-based chemotherapy. Over the past few decades, developments in immunotherapeutic strategies have provided newer insights into the treatment of gliomas. Immunotherapy is based on the principle of normalization or recovery of T cell-mediated anti-tumor immunoreaction. Different innovative strategies have been used; these include enhancement of immunogenicity by administration of tumor antigens or dendritic cell vaccines, replenishment of cytotoxic T cells by adoptive T cell transfer, repair of exhausted T cells by immune checkpoint inhibitors, and the use of other immune activators such as oncolytic viruses. However, many immunotherapy-based clinical trials did not meet the expected therapeutic endpoints in patients with glioma. Gliomas use unique strategies to generate an immune-suppressive microenvironment; these include limiting immunogenicity and repressing T cell infiltration or activation. This may be addressed by the incorporation of immunotherapy with standard therapy or by use of certain innovative approaches such as tumor-treating fields. In this review, we summarize the updated immunotherapies in glioma and discuss current limitations and future prospects.